THE IMPACT OF TRANSITION TO INTERNATIONAL GOVERNMENTAL ACCOUNTING STANDARDS ON THE QUALITY OF FINANCIAL REPORTING: A REVIEW - Sabah Hasan Mijbil, Shaymaa Nihro Jabal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The study aims to demonstrate the impact of the transition to international accounting standards in the public sector on the quality of financial reporting, as well as the role of the transition to international public sector accounting standards in achieving transparency and accountability and facilitating the process of integration with the international community, and to achieve the goal of the research, previous literature dealing with this has been reviewed. The topic and the study reached a set of conclusions, the most important of which are: The adoption of international accounting standards in the public sector leads to saving time, effort, and ease in comparing the financial statements of different government units, and that there is an increasing trend towards adopting international standards from some Iraqi government institutions, such as Diwan Financial Supervision and the Ministry of Finance.